2019
DOI: 10.1111/jir.12634
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the intellectual disability severity in the Spanish Personal Outcomes Scale

Abstract: Background The interest in measuring quality of life (QoL) in persons with intellectual disability (ID) has brought about a number of QoL measurements for this population. These measurements need to address two issues that have contributed to enhancing the current instruments. First, the necessity to develop measures with adequate psychometric properties, which has been discussed in recent studies, and second, the agreement between experts in analysing objective and subjective perspectives, as well as the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Our findings are congruent with those from previous studies, which suggest that observer reports may score people with more severe intellectual disability lower on certain QoL domains than the person would score themselves ( 20 ); this may also be a reflection of family input for people who have more severe-to-profound intellectual disability. This is demonstrated in Table 1 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are congruent with those from previous studies, which suggest that observer reports may score people with more severe intellectual disability lower on certain QoL domains than the person would score themselves ( 20 ); this may also be a reflection of family input for people who have more severe-to-profound intellectual disability. This is demonstrated in Table 1 .…”
Section: Discussionsupporting
confidence: 91%
“…The POS is somewhat unique in its measurement of QoL for people with an intellectual disability, as it: (1) is based on a QoL-specific theoretical framework; (2) assesses personal outcomes with guided support in a semi-structured format; and (3) considers multi-informant reporting. To date, studies to test the reliability and validity of the POS have been conducted in the Netherlands (14), Portugal (15)(16)(17)(18), Spain (19)(20)(21), and Italy (22). In terms of clinical outcomes within these studies, in Portugal it was found that living circumstances were related most to outcomes on the POS (16).…”
Section: Introductionmentioning
confidence: 99%
“…Modes of administration and sampling modes in these 40 studies were diverse including: cognitive interview [2], focus group [1], interviewer‐administered survey [24] of which two used a computer‐assisted programme [1] or interviewer‐administered modifications [1], self‐administered survey [14] with paper instrument [12], caregiver support or assisted completion [2], with visuals added [2], and with a pretest procedure to determine who could use a three‐point scale response option [1]. The topics of self‐report were varied among physical well‐being (Aznar et al, 2012; Balboni et al, 2013; Carbó‐Carreté et al, 2019; Pérez‐Cruzado & Cuesta‐Vargas, 2013; Schützwohl et al, 2018; Schwartz & Rabinovitz, 2003; Verdugo‐Alonso et al, 2017; Wigham et al, 2011; Wigham et al, 2014), mental well‐being (Benavidez & Matson, 1993; Bond et al, 2019; Dagnan et al, 2008; Esbensen et al, 2005; Gordon et al, 2007; Hall et al, 2014; Haynes et al, 2013; Hermans et al, 2012; Kellett et al, 2015; Masi et al, 2002; Mileviciute & Hartley, 2015; Penketh et al, 2014; Stancliffe et al, 2014; Watson et al, 1988), and social well‐being (Benromano et al, 2017; Bromley et al, 1998; Janeslätt et al, 2019; Johnson et al, 2014; Kellett et al, 2005; Kellett et al, 2015; Kramer et al, 2009; Liljenquist et al, 2019; Miller & Chan, 2008; Mumbardó‐Adam et al, 2018; O'Donovan et al, 2017; Pérez‐Cruzado & Cuesta‐Vargas, 2013; Perry & Felce, 2002; Turnpenny et al, 2018; Vlot‐van Anrooij et al, 2018; Walsh et al, 2018; Watkins et al, 2006) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…See Figure 1 (Watkins et al, 2006), and perceptions of pain (Benromano et al, 2017;Bromley et al, 1998) Quality of life (Balboni et al, 2013;Carb o-Carreté et al, 2019;Pérez-Cruzado & Cuesta-Vargas, 2013;Verdugo-Alonso et al, 2017), met/unmet needs (Schützwohl et al, 2018), life satisfaction (Schwartz & Rabinovitz, 2003), and adverse events and trauma (Wigham et al, 2011;Wigham et al, 2014). Mental health (Douma et al, 2006;Haynes et al, 2013;Hermans et al, 2013) concerns were self-reported including: depression (Benavidez & Matson, 1993;Esbensen et al, 2005;Gordon et al, 2007;Hall et al, 2014;Hermans et al, 2012;Kellett et al, 2015) and depressive symptoms (Mileviciute & Hartley, 2015), life events…”
Section: Key Questionsmentioning
confidence: 99%
“…UK data have therefore been collected from people with greater variability of severity of intellectual disability than those included in previous studies. Further analysis of the data collected in Spain examined the effect of severity of intellectual disability on individual item functioning and found that the scores of a significant number of items were affected by severity (Carbo‐Carrete et al, 2019 ). Authors suggest this indicates the need for broader discussion of the adequacy of definitions of QoL dimensions and indicators for the whole spectrum of people with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%